2012
DOI: 10.1029/2011jb008359
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of earthquake stress drop on critical slip‐weakening distance

Abstract: [1] Numerical simulations are conducted to investigate the dependence of the static stress drop of earthquakes on the critical slip-weakening distance. A fault model in a two-dimensional elastic medium is used, in which a locked zone (asperity) is assumed to exist between creeping zones. The presence of such a zone is commonly assumed for plate boundaries that have relatively low seismic coupling. Shear stress is concentrated at the edges of the locked zone and seismic rupture occurs when the strain energy rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…The possibility of step over jumps can be affected by relations between seismogenic depth and the long‐term average stress at which a fault operates. In earthquake cycle models of faults loaded by deep creep (Kato, ), it is found that as W increases the average stress decreases. Fracture mechanics analysis of this problem leads to a relation that can be formulated as S+1W/Lc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of step over jumps can be affected by relations between seismogenic depth and the long‐term average stress at which a fault operates. In earthquake cycle models of faults loaded by deep creep (Kato, ), it is found that as W increases the average stress decreases. Fracture mechanics analysis of this problem leads to a relation that can be formulated as S+1W/Lc.…”
Section: Discussionmentioning
confidence: 99%
“…The fundamental results assuming homogeneous initial stress presented here can help understand the outcomes of such more complete models. For example, we expect initial shear stress to be mostly concentrated near the deep edge of the seismogenic zone due to creep on the deeper portion of the fault (see, e.g., Figure 1 of Kato, ). If this stress concentration is substantial, we should observe a tendency for ruptures on secondary faults to initiate in the deepest part of the seismogenic zone.…”
Section: Discussionmentioning
confidence: 99%
“…Although some uncertainty is included in estimates of D c for earthquakes, D c of 1.5–2.0 m seems to be permissible [e.g., Zhang et al , 2003]. The recurrence interval T r of great earthquakes is controlled by fracture energy at the strong patch and the theoretical consideration suggests that T r is proportional to [ Kato , 2010]. We perform numerical simulations for various values of friction parameters to confirm that qualitatively similar results can be obtained for only higher σ n eff or only larger L at the shallow patch, though too large L leads to slow earthquakes or stable sliding [ Kato and Hirasawa , 1997].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…We point out that the definition of earthquake used here (based on a velocity threshold) probably does not accurately reflect the way seismic ruptures are recorded, making it difficult to directly translate our results into observable variations in source properties. In fact, a similar study by Kato (2012b) found constant stress drops for ruptures nucleating at the center, the discrepancy most likely explained by the use of a lower velocity threshold (0.01 m/s), which resulted in part of…”
Section: Observations Near the Nucleation Dimensionmentioning
confidence: 94%